ANALYSIS OF FEMALE CRIMINALITY AND ITS GLOBAL AND LOCAL SOCIAL THREATS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article presents the facts that crime is a historically changeable social and criminal law phenomenon, which is a system of crimes committed in a given country (region) over a certain period of time. Information is given that crime is considered the most dangerous type of "social pathology", about the influence of legal norms on increasing and demonstrating the importance of a person's official activity, crime prevention and identification and disclosure of the causes of crimes committed.